2022
DOI: 10.3389/fpsyt.2022.779239
|View full text |Cite
|
Sign up to set email alerts
|

Are There Neural Overlaps of Reactivity to Illegal Drugs, Tobacco, and Alcohol Cues? With Evidence From ALE and CMA

Abstract: Abuses of most illegal drugs, including methamphetamine, marijuana, cocaine, heroin, and polydrug, are usually in conjunction with alcohol and tobacco. There are similarities and associations between the behavior, gene, and neurophysiology of such abusers, but the neural overlaps of their cue-reactivity and the correlation of neural overlap with drug craving still needs to be further explored. In this study, an Activation Likelihood Estimation (ALE) was performed on brain activation under legal (tobacco, alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 109 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…A third limitation is that reactivity to alcohol/drug images was defined in relation to reactivity to affectively neutral complex images (i. e., ACR=Alc-CC). Although such contrasts are widely used in the alcohol/drug cue fMRI literature [ 44 , 50 , 51 , 72 , 95 ], it is important to note that alternative contrasts (e.g., alcohol/drug images vs. non-alcohol/drug reward images) may be better suited for delineating neural mechanisms or biomarkers of addiction [ 96 , 97 ]. Here, these alternative contrasts (e.g., Alc-FD) did not return voxel clusters that survived family-wise error (FWE) correction to p <.05.…”
Section: Discussionmentioning
confidence: 99%
“…A third limitation is that reactivity to alcohol/drug images was defined in relation to reactivity to affectively neutral complex images (i. e., ACR=Alc-CC). Although such contrasts are widely used in the alcohol/drug cue fMRI literature [ 44 , 50 , 51 , 72 , 95 ], it is important to note that alternative contrasts (e.g., alcohol/drug images vs. non-alcohol/drug reward images) may be better suited for delineating neural mechanisms or biomarkers of addiction [ 96 , 97 ]. Here, these alternative contrasts (e.g., Alc-FD) did not return voxel clusters that survived family-wise error (FWE) correction to p <.05.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed high percentage of alcohol consumption and dependence (90.1% and 21.2%, respectively), which exceeded the levels reported by the WHO for the general population of the American region. Considering that the abuse of most illegal drugs, including methamphetamine, cannabis, cocaine, heroin, and polydrugs, generally occur in conjunction with alcohol, intervention strategies should not exclude legal drugs in their communication aspects, especially considering the risks associated with polydrug use and the interaction between PS [ 43 ]. Cannabis was predominantly used by the surveyed population.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the abuse of most illegal drugs, including methamphetamine, cannabis, cocaine, heroin, and polydrugs, generally occur in conjunction with alcohol, intervention strategies should not exclude legal drugs in their communication aspects, especially considering the risks associated with polydrug use and the interaction between PS [43]. Cannabis was…”
Section: Plos Onementioning
confidence: 99%